Epistemology of PMI Dawah Science Based on Social Welfare (Social Welfare) - Hidayatulloh, Asep; Syukur, Abdul (STAI Miftahul Ula Nganjuk, 2022)
This study delves into the epistemology of Da'wah Science as applied by the Center for the Study of Islamic Community Development (PMI), focusing on the socially welfare-based approach known as